Valikhanov and the epos of turkish peoples (Eurasian Journal of Philology Science and Education, 2021)
The article is devoted to Turkic epic studies. It reveals the key role of Ch. Ch. Valikhanov – an epic scholar. His valuable observations of oral traditions of the Kazakhs, Kyrgyz and tribes of Southern Siberia still cover current issues regarding world epic studies. The main purpose of the article is to reveal methodological significance of the scientist’s results. The value of his approaches lies in anticipation of many ways of oral theory, since he studied the word “from within the tradition itself” both as a native Turkic languages speaker and as an Orientalist, operated with the sciences methods of the time. He was clearly aware of the unique richness of centuries-old Great Steppe knowledge – the Turks epos of the North Caucasus, Central Asia, and Southern Siberia. The Turkic tradition first appeared in his works in all its genre and species richness, serving as the subject and object of his research and comply with the key points of the oral theory of Parry M. and Lord A.: the nature of the creator and performer, the transmission of oral legend, the issue of authorship, nationality, etc. The leading school of modern folklore studies – the oral theory of Parry M. and Lord A. – and the productive ideas of Ch. Ch. Valikhanov define a new way of studying the Turks epos, brining it back to its original foundations: archaic myth, rite and ritual. The scientist’s view of the oral tradition “from within” the tradition itself and his historical and ethnographic approach in the interpretation of the epos of the Turkic peoples are of current importance.